Educational and Occupational Opportunity in the Canadian Mosaic - Porter, John (Canadian Journal of Counselling and Psychotherapy, 2012)
Three aspects of social change which create a challenge for guidance counsellors are examined. It is argued that the current emphasis on ethnic identity is inappropriate in a post-industrial society, and it is suggested that the counsellor should provide a bridge to the opportunity structure for children from cultures that do not value education or achievement. The fact that they do not is illustrated by data from a survey of Ontario high school students which shows a close relationship between social class and educational aspirations. Guidance counsellors also have an important role in advising girls in the light of the demand for equality on the part of women and the continuing low educational aspirations of girls as shown in the data from the survey of Ontario students. The third change which affects the counsellor is the downgrading of certification in the educational system. It is argued that it is regressive in its effect on lower class children since it deprives them of one of the most important instruments of upward mobility, the certificate of achievement.